ERC-ESICM guidelines on temperature control after cardiac arrest in adults. (March 2022) - Nolan, Jerry P.; Sandroni, Claudio; Andersen, Lars W.; Böttiger, Bernd W.; Cariou, Alain; Cronberg, Tobias; Friberg, Hans; Genbrugge, Cornelia; Lilja, Gisela; Morley, Peter T.; Nikolaou, Nikolaos; Olasveengen, Theresa M.; et al.
Abstract: The aim of these guidelines is to provide evidence‑based guidance for temperature control in adults who are comatose after resuscitation from either in-hospital or out-of-hospital cardiac arrest, regardless of the underlying cardiac rhythm. These guidelines replace the recommendations on temperature management after cardiac arrest included in the 2021 post-resuscitation care guidelines co-issued by the European Resuscitation Council (ERC) and the European Society of Intensive Care Medicine (ESICM). The guideline panel included thirteen international clinical experts who authored the 2021 ERC-ESICM guidelines and two methodologists who participated in the evidence review completed on behalf of the International Liaison Committee on Resuscitation (ILCOR) of whom ERC is a member society. We followed the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach to assess the certainty of evidence and grade recommendations. The panel provided suggestions on guideline implementation and identified priorities for future research. The certainty of evidence ranged from moderate to low. In patients who remain comatose after cardiac arrest, we recommend continuous monitoring of core temperature and actively preventing fever (defined as a temperature > 37.7 °C) for at least 72 hours. There was insufficient evidence to recommend for or against temperature control at 32–36 °C or early cooling after cardiac arrest. We recommend not actively rewarming comatose patients with mild hypothermia after return of spontaneous circulation (ROSC) to achieve normothermia. We recommend not using prehospital cooling with rapid infusion of large volumes of cold intravenous fluids immediately after ROSC.